Two monsters - Ivaldi, Cristina; Decataldo, Claudio (Genoa [Italy] : Black Cat, 1999)
A clean bogey boy and a messy human boy decide to change places and live with the other's family. Includes activities.
Compact disc.
5.0
5-8
Keywords: Readers (Elementary).; Readers; Compact discs; Reading materials; Compact discs